A Panoramic Review of the Macromarketing Literature - DeQuero-Navarro, Beatriz; Stanton, Julie; Klein, Thomas A. (Journal of macromarketing, 2021)
This contribution benchmarks the 40th anniversary issue of the Journal of Macromarketing with an updated and topically organized bibliography of articles that can be used by interested researchers and in university courses devoted to or including a survey of this subject. Fisk (1990), Shapiro (2006), and Shapiro, Tajadewski, and Shultz (2009) have provided previous renditions of this sort. However, the topical arrangement differs from these earlier efforts and instructive introductions are provided for each of the 13 broad topic sections proposed. References provided in the articles listed below them would extend sources for these topics. Our goal was to provide recency as well as variety in focus and methodology throughout Macromarketing literature, including both long-standing and emerging areas of interest.